The pattern of glaciation on the Avalon Peninsula of Newfoundland - Catto, Norm (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThe pattern of glaciation on the Avalon Peninsula has been established through study of geomorphic features, striations, and erratic provenance. Three phases in a continuum of glaciation are recognized. The initial phase involved the expansion of ice from several centres. Ice thickness and extent reached a maximum during the subsequent Phase 2 event, correlated with the Late Wisconsinan. Lowered sea level permitted the development of the St. Mary's Bay ice centre. Ice from the Newfoundland mainland coalesced with Avalon Peninsula ice inPlacentia Bay, on the Isthmus, and in Trinity Bay. Rising sea level, triggered by the retreat of Laurentide ice in Labrador, resulted in destabilization of the St. Mary's Bay ice cap, marking Phase 3. Final deglaciation of theAvalon Peninsula began before 10,100 ± 250 BP. The Avalon Peninsula ice caps were controlled by regional and hemispheric events, and by the response of the Lauren- tide glaciers.